The Ancient Mesopotamian Mīs Pî Ritual: An Application of the Ecological Anthropology of Roy Rappaport - Balogh, Amy L. (2021)
This article presents the ancient Mesopotamian Mīs Pî ceremony as a case study in the relationship between ritual and the natural world using Roy Rappaport’s framework of Ecological Anthropology as a guide. Rappaport’s premise is that human populations do not operate independently but are instead, “ecological populations in an ecosystem that also includes the other living organisms and the nonliving substances found within the boundaries of [their] territory.” In Rappaport’s framework, rituals involving the use of animal, plant, and other organic materials link human communities to the ecosystems in which they dwell and to that which they seek to ritualize. Applying this mode of analysis to the Mīs Pî ritual yields the thesis that, from the perspective of the Mīs Pî, nature is integral to the ritual maintenance and well-being of the divine and human realms, and, in effect, the well-being of the cosmos.
Keywords: Roy Rappaport; nature in ancient religion; Purification; Mis Pi ceremony; ecological anthropology; Ritual